The Legal Ruling on Using Gelatin Derived from Pork (Islamic Sciences Journal, 2023)
ABSTRACT                                    The development taking place in the food and pharmaceutical industries dictated the use of some materials that scholars disputed about their solution and their prohibition, and Among these materials is gelatin extracted from pork fat, which has been widely used in the pharmaceutical, health, and cosmetic industries and others, and some of these products cannot be substituted for a Muslim who is in Islamic countries or elsewhere. This research included two topics: The first topic: the uses of pork derivatives, the second topic: the legal position on the uses of pork derivatives, then the conclusion of the research, and the index of sources and references. The research reached to  the prohibition of using pork derivatives except when there is a compelling necessity as its use in medicine.
Keywords: Pig derivatives, the legal position, Abu Hayyan, Ibn Attia, the view of Al-Shawkani .